Consumer attitude towards Pakistani Clothing Brands on Facebook before and during Covid-19 pandemic - Amjad, Ahmad; Farman Ali; Gulam Farroque; Fatima Nawaz; Fahad Assad (UMT Artificial Intelligence Review, 2022)
COVID-19 has drastically affected businesses, industries, and consumers across the world. However, the rise of digital technology and advancements in e-commerce sector in the past decade has helped clothing brands to cope-up with the pandemic challenges. These developments have also shifted the perspective of founders to the new normal. This research paper provides a consumer oriented analysis of how clothing brands and consumers in Pakistan have reacted to the pandemic. Consumer reactions on these platforms are analyzed, including social media marketing and purchasing of clothes on Facebook. Specifically, it focuses on the first wave of COVID-19 as it provides core insights into business transformations from the perspectives of both business organization and consumers. Although, the situation has been appreciably restored now.